Selection of a method for calculating heat gain from solar radiation to determine the load on the climate system of the cabin of a mobile car - V. V. Maslenskiy (Безопасность техногенных и природных систем, 2021)
Introduction. The article analyzes and selects the most rational methods for calculating the heat gain from solar radiation. The correct calculation of this component of the heat balance allows you to correctly determine the power of the projected cabin climate system, which will ensure optimal working conditions at the workplace of mobile car operators.Problem Statement. The objective of this study is to analyze and select a rational method for calculating heat gain from solar radiation for the correct determination of the thermal load on the climate system of the cabin of a mobile car.Theoretical Part. To implement the task, the most common methods for calculating solar radiation were described and analyzed in detail and the most accurate ones were recommended.Conclusions. The more labor-intensive method of V.N. Bogoslovskiy (taking into account the time of day) can be recommended for automated calculations in Excel, and the method of P.Y. Gamburg (taking into account the sides of the horizon) — for comparative estimated engineering calculations. When conducting "in-depth" model calculations and accounting for solar radiation, the ASHRAE method is explicitly suitable, which has two important advantages: it takes into account the solar factor in relation to a specific type of glazing and is adapted for automated calculations in ANSYS FLUENT.